(untitled) (Orfeu, 2022)
The aim of this study is to make perceptible the senses and meanings of the narrative of a graduate student, in order to understand how her choice for the music teaching profession occurred. The autobiographical essays, oral and written, understood as a training practice and research method, were produced during fifteen weeks in a course of the master’s course in music education, offered during 2019. Ten themes were addressed: choice of profession; family, musical, and educational background; being a teacher and musician; professional performance with music; musical learning; music in the school context; outstanding formative experiences; experiences with composition and improvisation; experiences with non-formal music education; and, how musical experiences relate to theoretical studies and epistemological views of authors in the fields of education and, especially, music education. To present Giulliana’s story, a series of cuts were made to allow looking at her trajectory beyond the biographical journey. The question that guided this research was: what was process of deciding to become a music teacher? In interpreting the narratives, the relationships between the personal and professional dimensions that led to her educational choices were highlighted, as well as the processes of change that are reflected in her life story. The axes selected for discussion were the early school years, musical experiences and training, and the decision for music education. It is a singular story that intends, above all, to be educational.